Varicella zoster virus infection causing urinary retention in a child with HIV infection - G S Wessels; C F Heyns (AOSIS, 2012)
An 11-year-old boy receiving antiretroviral therapy for HIV infection and antibacterial therapy for pulmonary tuberculosis presented with urinary retention due to varicella zoster virus infection involving the sacral nerves, confirmed on serological testing. The perineum over dermatomes S2 - S4 on the left was involved with a vesicular and superficially erosive rash. A transurethral catheter was inserted and the patient was treated with acyclovir (300 mg 6-hourly for 5 days). At follow-up 4 weeks later, the perineal skin lesions had healed, the catheter was removed and the patient was able to pass urine.